Determination of Volatile Compounds in Four Commercial Samples of Japanese Green Algae Using Solid Phase Microextraction Gas Chromatography Mass Spectrometry. (27th January 2014) - Yamamoto, Masayoshi; Baldermann, Susanne; Yoshikawa, Keisuke; Fujita, Akira; Mase, Nobuyuki; Watanabe, Naoharu
Abstract : Green algae are of great economic importance. Seaweed is consumed fresh or as seasoning in Japan. The commercial value is determined by quality, color, and flavor and is also strongly influenced by the production area. Our research, based on solid phase microextraction gas chromatography mass spectrometry (SPME-GC-MS), has revealed that volatile compounds differ intensely in the four varieties of commercial green algae. Accordingly, 41 major volatile compounds were identified. Heptadecene was the most abundant compound from Okayama ( Ulva prolifera ), Tokushima ( Ulva prolifera ), and Ehime prefecture ( Ulva linza ). Apocarotenoids, such as ionones, and their derivatives were prominent volatiles in algae from Okayama ( Ulva prolifera ) and Tokushima prefecture ( Ulva prolifera ). Volatile, short chained apocarotenoids are among the most potent flavor components and contribute to the flavor of fresh, processed algae, and algae-based products. Benzaldehyde was predominant in seaweed from Shizuoka prefecture ( Monostroma nitidum ). Multivariant statistical analysis (PCA) enabled simple discrimination of the samples based on their volatile profiles. This work shows the potential of SPME-GC-MS coupled with multivariant analysis to discriminate between samples of different geographical and botanical origins and form the basis for development of authentication methods of green algae products, including seasonings.